An analysis of the distribution and spectrum of alpha thalassemia mutations in Rasht City, North of Iran - Asghari Ahmadabad, Mona; Pourreza, Noushin; Ramezanpour, Setareh; Baghersalimi, Adel; Enshaei, Mersedeh; Askari, Marjan; Alizadeh, Amirhossein; Izadi, Elahe; Darbandi, Bahram (Frontiers in Pediatrics, 2023)
Background Alpha thalassemia is one of the most common hereditary hemoglobin disorders worldwide, particularly in the Middle East, including Iran. Therefore, determining the spectrum and distribution of alpha thalassemia mutation is a fundamental component of preventive approaches and management strategies. Methods The present study reviews the genetic testing and blood laboratory results of 455 candidates eligible for marriage who were suspected of being thalassemia carriers and on whom genetic testing was performed from 21 March 2013 to 31 December 2020 in Rasht City. Results A total of 114 (25.05%) alpha thalassemia cases were identified. Fifteen different alpha mutations were found. The most common mutation among the study population was −α3.7 deletion in 55 patients (48.24%), followed by Hb Constant Spring (C.S) in 21 patients (18.42%) and poly A2 in 16 (14.03%). Also, most of the patients were silent carriers. The deletion type of mutation was much more common than non-deletion mutations. Conclusion Our study reveals genetic heterogeneity and alpha thalassemia diversity among the Rasht City population. We expect that these findings will help guide premarital screening and genetic counseling, prenatal diagnosis of thalassemia, preventive strategy development, as well as a compilation of the alpha thalassemia catalog in Guilan province.